THE ROLE OF MONITORING IN THE FORMATION OF THE PROFESSIONAL COMPETENCIES OF FUTURE TEACHERS EDUCATIONAL BRANCH "TECHNOLOGY" - T.A. Khoruzhenko (Academy of Cognitive and Natural Sciences, 2008)
The level of formed professional competence comes precondition of efficiency pedagogical activity teacher at school. In clause the role of monitoring in forming professional competence future teachers of educational industry "Technology" are considered.